2020
DOI: 10.1080/21645698.2020.1831728
|View full text |Cite
|
Sign up to set email alerts
|

What type of Bt corn is suitable for a region with diverse lepidopteran pests: A laboratory evaluation

Abstract: Transgenic crops that produce Bacillus thuringiensis (Bt) toxins are effective tools for controlling lepidopteran pests. However, the degree of susceptibility to Bt toxins differs among various pest species due to relatively narrow spectrum and high selectivity of such toxins. Bt corn hybrids for Chinese market were designed to target Asian corn borer Ostrinia furnacalis (Guenée), while their efficacy against other lepidopteran pests are not well defined, such as Conogethes punctiferalis (Guenée), Helicoverpa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…A high‐dose/refuge strategy has been shown to be effective in mitigating the evolution of resistance in fall armyworm in the USA 25,39,40 . Our previous study showed that the relative susceptibility indexes of fall armyworm to Cry1Ab, Cry1Ac, Cry1F, Cry2Ab, and Vip3A proteins ranged from 0.28 to 3.76 compared with a susceptible population in the USA, 42,72 and genetic characterization analysis also found no reported Bt resistance mutation loci for the fall armyworm population in China, 73 which is favorable for fall armyworm management using Bt corn. Given the performance of DBN3601T corn against fall armyworm in field trials, it seems likely that DBN3601T event corn provides inadequate control to meet the criteria of high‐dose (concentration causing mortality at least at the 25× lethal concentration of 99% (LC99) level 74 ).…”
Section: Discussionmentioning
confidence: 99%
“…A high‐dose/refuge strategy has been shown to be effective in mitigating the evolution of resistance in fall armyworm in the USA 25,39,40 . Our previous study showed that the relative susceptibility indexes of fall armyworm to Cry1Ab, Cry1Ac, Cry1F, Cry2Ab, and Vip3A proteins ranged from 0.28 to 3.76 compared with a susceptible population in the USA, 42,72 and genetic characterization analysis also found no reported Bt resistance mutation loci for the fall armyworm population in China, 73 which is favorable for fall armyworm management using Bt corn. Given the performance of DBN3601T corn against fall armyworm in field trials, it seems likely that DBN3601T event corn provides inadequate control to meet the criteria of high‐dose (concentration causing mortality at least at the 25× lethal concentration of 99% (LC99) level 74 ).…”
Section: Discussionmentioning
confidence: 99%
“…The oriental armyworm Mythimna separata (Walker), the bollworm Helicoverpa armigera (Hübner), and the fall armyworm Spodoptera frugiperda (J. E. Smith) are three major species of Lepidoptera insects that seriously affect global maize production. As a polyphagous, long-distance migratory, and sporadic corn pest, M. separata is notorious for its high feeding levels and can devour all available leaves when it abruptly outbreaks [ 2 , 3 , 4 ]. H. armigera is a widely distributed omnivorous pest that can migrate over long distances, and mainly feeds on leaves, silks, ears, and grains, thereby wreaking havoc on pollination, inducing ear rot, and reducing grain quality [ 2 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…DBN9936 and Ruifeng 125. Considering how maize‐feeding lepidopterans such as S. frugiperda are susceptible to Bt toxins (Li et al ., 2021 ), these maize varieties can lower pesticide usage intensity but concurrently trigger Bt resistance evolution. Non‐Bt maize refugia can delay resistance evolution (Hutchison et al ., 2010 ; Tellez‐Rodriguez et al ., 2014 ) and are implemented through seed mixtures of Bt and non‐Bt cultivars at the appropriate ratio also termed ‘refuge‐in‐the‐bag’ or structured refuges, i.e.…”
Section: Introductionmentioning
confidence: 99%